Remote teaching during the pandemia: narratives of brazilian undergraduate Public Relations faculty (Olhar de Professor, 2021)
The study presents the challenges met by Public Relations faculty during the deployment of remote teaching formats required by the social distancing imposed by the COVID19 pandemic, and the adaptations of contents required by the full utilization digital technologies. The opinions of 121 Public Relations faculty were ascertained through the use of a survey grouped in accordance with four challenges encountered, namely: (a) familiarity and adaptation to the use of digital technologies; (b) the interest and lack of interest shown by students to the remote teaching format; (c) teaching behavior in the home environment; (d) missing training and/or guidance given by the institution of higher education. It was concluded that despite the challenges encountered, Public Relations faculty demonstrated a fundamental role in the continuity of PR teaching programs despite the over burdening of domestic, work-related and family issues.
Keywords: Remote learning. Digital platforms. Public Relations. Teaching-learning process. Faculty training.